Perceived Overqualification and Collectivism Orientation: Implications for Work and Nonwork Outcomes. (February 2022) - Luksyte, Aleksandra; Bauer, Talya N.; Debus, Maike E.; Erdogan, Berrin; Wu, Chia-Huei
In this research, we simultaneously examined the relative applicability of person-environment fit and relative deprivation theories in explaining the interactive effects of perceived overqualification and collectivism cultural orientations on positive outcomes. We hypothesized that the negative (positive) influence of perceived overqualification on person-environment fit (relative deprivation) will be weaker among employees with high collectivism cultural orientation. We also examined which of these two different mechanisms would explain the hypothesized interactive effects in predicting these workers' citizenship behavior, personal initiative, work engagement, and life satisfaction. We tested our hypotheses in two studies. In Study 1, we recruited professional staff (n = 852) and their coworkers (n = 301) from 95 universities and tested our hypotheses in a matched sample of 190 employees and their peers. The moderated mediation results supported the idea of person-environment fit (but not relative deprivation) as the mechanism explaining why collectivism orientations assuaged the negative effects of perceived overqualification on these outcomes. We constructively replicated these results in Study 2, which was a time-lagged design with full-time employees (n = 224). Study 2's results further supported the robustness of our model by testing alternative moderators, mediators, and outcomes.